Effect of exogenous iodine on enhancement of oxidative stress in soybean (Glycine max) plant and partial expression of 1-Cys peroxiredoxin gene under heat-stress conditions - NEHA GUPTA; MONIKA SHUKLA BAJPAI; RITA SINGH MAJUMDAR; DINESH SINGH (The Indian Journal of Agricultural Sciences, 2016)
The present study analyzes the biochemical effects of exogenous iodine on the antioxidant defense system of soybean (Glycine max L.) plant when grown under heat stress (35ºC). The parameters studied under oxidative stress generation were superoxide anion production, hydrogen peroxide formation and malondialdehyde production. The enzymatic defense was investigated by analyzing the levels of superoxide dismutase, ascorbate peroxidase, catalase and glutathione reductase. For the partial expression of 1-cys peroxiredoxin, the genomic DNA was extracted and primers were designed to amplify the 3’ end region of the PER-1 gene locus 17780502 to 17781727 of genome size 61Mbp,  304  base  pairs:  PER1-F  5’-ATGCCAGGGATCACACTAGG-3’and  PER1-R  5’-ACAAGACAGACCAAGGAGCT-3’ and subjected to PCR. The heat stress generated maximum malondialdehyde without application of iodate and production of superoxide anion was maximum in 80 µM iodate concentration. The H2O2 production was reported highest in 40 µM iodate concentration, Enzymatic defense was highest in 20 and 80 µM dosages of iodate. We amplified 1-cys peroxiredoxin (1-Cys Prx) gene, an important antioxidant enzyme, in soybean plant using primer of an Arabidopsis 1-Cys Prx gene to confer tolerance against heat stress.